The Role Of Knowledge Management Systems In Improving The Performance Of Educational Institutions "A Field Study At Latakia University Hospital" (Latakia University (formerly Tishreen)Journal for Research and Scientific Studies - Economic and Legal Sciences Series, 2026)
The research problem stemmed from observing shortcomings in the application of Knowledge Management Systems at Latakia University Hospital and the potential negative implications of this deficiency on the performance of educational institutions within it. The study aimed to identify the role of Knowledge Management Systems in improving institutional performance by analyzing their technological, organizational, human, and administrative dimensions and measuring their impact on efficiency and effectiveness.The research adopted the descriptive-analytical approach, as it is appropriate to the nature of the study. The theoretical framework was developed based on Arabic and foreign references, and a questionnaire was designed and reviewed by a panel of experts to ensure its validity and reliability. Data were analyzed using SPSS (Version 20) to examine the relationships among the study variables.The findings revealed a general weakness in the level of Knowledge Management Systems implementation, as the mean scores were below (3), indicating deficiencies in the institutional knowledge infrastructure. The study recommended developing an integrated Knowledge Management framework, strengthening technological infrastructure, integrating knowledge management into the organizational structure and strategy, investing in human resource development, and reinforcing leadership support to enhance institutional efficiency and effectiveness.
Keywords: Knowledge Management Systems, Technological Dimension, Organizational Dimension, Human Dimension, Performance Of Educational Institutions.